PENGEMBANGAN PROTOTIPE AUGMENTED REALITY DAN INTERNET OF THINGS (AR-IOT) UNTUK PERAWATAN MESIN INDUSTRI - Agus Wagyana; Dandun Widhiantoro; M. Reza Febrian; Purbo Dwi Junianto, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Industrial machine maintenance plays an important role in ensuring continuous production. Common issues such as delayed fault detection, lack of real-time data, and reliance on technician expertise can lead to costly downtime. This study proposes a prototype system that integrates Augmented Reality (AR) and the Internet of Things (IoT), known as AR-IoT, for efficient industrial machine monitoring and control. The system is built using an ESP32 microcontroller that collects temperature, vibration, and pressure data through LM35, ADXL345, and MPS20N0040D sensors. The sensor data is transmitted via Wi-Fi to the MQTT broker (HiveMQ Cloud), and displayed in real-time through an AR interface developed with Unity and Vuforia. The interface allows users to monitor sensor data and control actuators such as relays and alarms interactively. The system also utilizes Firebase for cloud data storage. Experimental results show that the AR-IoT system functions stably and responsively, with successful integration between AR visualization and IoT-based control. The developed prototype demonstrates the potential of AR-IoT systems in improving maintenance accuracy, responsiveness, and operational efficiency in industrial settings.